Administration of polysaccharide from Panax notoginseng prolonged the survival of H22 tumor-bearing mice - Li, Huaiyu (Onco Targets Ther, 2016)
BACKGROUND: Polysaccharides from various sources are being considered potential sources for the treatment of liver cancer. The aim of this study was to investigate the impact of polysaccharide isolated from Panax notoginseng (PPN) on the proliferation of H22 liver cancer cells and the survival of the tumor-bearing mice transplanted with H22 cells. MATERIALS AND METHODS: Polysaccharide from PPN was added to the culture medium of mouse hepatoma H22 cells at different doses. Cell proliferation was assayed with a standard MTT assay. Survival rates of tumor-bearing mice were recorded. Peripheral blood lymphocytes were assayed by flow cytometry. Serum interleukin-2 levels in peripheral blood were measured by enzyme-linked immunosorbent assay. RESULTS: Polysaccharide from PPN inhibited the growth of H22 cells and significantly prolonged the survival of tumor-bearing mice. The increase in activated CD4(+) T-cells and the elevation of serum interleukin-2 may contribute to the antitumor activity of PPN. CONCLUSION: PPN has potential antitumor activity for the treatment of liver cancer.